2004
DOI: 10.1172/jci20742
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α is crucial for the development of autoimmune arthritis in IL-1 receptor antagonist–deficient mice

Abstract: IL-1 receptor antagonist-deficient (IL-1Ra -/-) mice spontaneously develop autoimmune arthritis. We demonstrate here that T cells are required for the induction of arthritis; T cell-deficient IL-1Ra -/-mice did not develop arthritis, and transfer of IL-1Ra -/-T cells induced arthritis in nu/nu mice. Development of arthritis was also markedly suppressed by TNF-α deficiency. We found that TNF-α induced OX40 expression on T cells and blocking the interaction between either CD40 and its ligand or OX40 and its liga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
90
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 114 publications
(96 citation statements)
references
References 28 publications
(14 reference statements)
5
90
1
Order By: Relevance
“…Arthritis in these mice arises from disturbed immune homeostasis due to excessive IL-1 signaling, which results in the induction of costimulatory molecules such as OX40 and CD40 ligand on T cells, thereby enhancing APC-T cell interaction and mediating T cell autoimmunity (26,27). For therapeutic treatment of IL-1Ra Ϫ/Ϫ mice, we chose a lower dose but a longer treatment course than that for existing CIA because of the milder joint destruction and the more chronic progress of arthritis in this model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arthritis in these mice arises from disturbed immune homeostasis due to excessive IL-1 signaling, which results in the induction of costimulatory molecules such as OX40 and CD40 ligand on T cells, thereby enhancing APC-T cell interaction and mediating T cell autoimmunity (26,27). For therapeutic treatment of IL-1Ra Ϫ/Ϫ mice, we chose a lower dose but a longer treatment course than that for existing CIA because of the milder joint destruction and the more chronic progress of arthritis in this model.…”
Section: Discussionmentioning
confidence: 99%
“…The protective effects of the TLR-4 antagonist in CIA were not mediated by a disruption of the adaptive immune response disturbing the development of autoimmunity in this model. In addition, treatment with the TLR-4 antagonist reduced the clinical and histopathologic features of arthritis in IL-1Ra Ϫ/Ϫ mice, in which an autoimmune T cell-mediated arthritis develops spontaneously due to unbalanced IL-1 signaling (26,27).…”
mentioning
confidence: 99%
“…Excess IL-1␤ signal induced the increased production of IL-23 in IL-1Ra Ϫ/Ϫ mice compared with its effects in WT mice. Iwakura and colleagues (22)(23)(24) have reported that IL-1Ra Ϫ/Ϫ mice that are also deficient in IL-17 or TNF-␣ do not develop spontaneous arthritis. Interestingly, they found that IL-1 does not directly induce the production of IL-17 or TNF-␣ by CD4 ϩ T cells.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of autoantibodies directed against Ig, type II collagen, and dsDNA are detectable in serum (22). In this model, excess IL-1 signaling due to a deficiency in the IL-1Ra causes T cell-mediated autoimmunity, resulting in joint-specific inflammation and bone destruction (22)(23)(24). IL-17 expression is greatly enhanced in IL-1Ra Ϫ/Ϫ mice, suggesting that IL-17 activity is involved in the pathogenesis of arthritis in these mice.…”
Section: Stat3 and Nf-b Signal Pathway Is Required For Il-23-mediatedmentioning
confidence: 95%
“…It is rare for IL-1ra -/-mice to develop arthritis in all four paws, thus the arthritis score seldom reaches the maximum. T and B cells are important for the spontaneous development of arthritis in IL-1ra -/-mice and the involvement of OX-40 and CD40L is suggested [18]. IL-17 production from T cells has been shown to play a crucial role in the spontaneous development of arthritis in IL-1ra -/-mice [19].…”
Section: Introductionmentioning
confidence: 99%